Al-Tikrār and Al-Tadrīj: Pesantren Learning Method TGH Bagu Lombok NTB - Fadli, Adi (Jurnal Pendidikan Islam, 2018)
TGH Bagu is known as a charismatic figure and agent of change in Islamic education in Lombok NTB. He is an Islamic education reformer. The huge honors TGH Bagu is a manifestation of thought that must be appreciated in pesantren education. The masterpiece acts TGH. Bagu is developing the foundation of Qomarul Huda School. The School foundation uses curriculum methods for improving learning models. This paper talks about a curriculum In Qomarul Huda school in pesantren with the Teaching-learning repetitions method (al-Tikrār) and logic method (al-Tadrīj).